First one stays the same: -3/(x+1)
2x/(-x-1) = -2x/(x+1)
So on top you now have:
-3/(x+1) + 2x/(x+1) = (2x-3)/(x+1)
----------
Bottom:
-10/(x+1) is fine
You need to get a common denominator for the 4...
4(x+1)/(x+1) = (4x + 4)/(x+1)
So now you have:
-10/(x+1) + (4x+4)/(x+1) =
(4x - 6)/(x+1) =
[2(2x - 3)]/(x+1)
----------
when you have (a/b)/(c/d) = ad/bc
So...
[(2x-3)(x+1)]/[(x+1)(2)(2x - 3)]
The (x+1) and (2x -3) on top and bottom cancel.
You're left with 1/2
2007-01-26 10:49:08
·
answer #1
·
answered by Mathematica 7
·
0⤊
0⤋
(5z ? 5)/21 ÷ (z ? a million)/(14z) = First, attempt to confirm if something factors out. interior the staggering of the 1st fraction (z ? a million) factors out. In the two fractions 7 factors out. (5z ? 5)/21 ÷ (z ? a million)/(14z) = 5(z ? a million)/(3·7) ÷ (z ? a million)/(2·7z) = Divide the staggering and cancel out the backside. 5(z ? a million)/(3·7) ÷ (z ? a million)/(2·7z) = 5/3 ÷ a million/(2z) = Now that is somewhat much less perplexing. we alter ÷ into · (branch into multiplication) and turn the 2d fraction over getting its reciprocal. 5/3 ÷ a million/(2z) = 5/3 · 2z = Multiply. 5/3 · 2z = 10/3 z = Divide the staggering (10) by utilising the backside (3). 10/3 z = 3.(3) z
2016-11-01 09:12:47
·
answer #2
·
answered by gennusa 4
·
0⤊
0⤋
Numerator = - 3/(x+1) +2x/(x+1) =(2x - 3)/(x+1).
Denominator = (4x-6)/(x+1) =2(2x -3) /(x+1)
So the desired fraction = (1/2) Answer.
2007-01-26 11:02:32
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
start with the top --> make a constant denominator and subtract them
do the same with the bottom
you'll be left with two fractions -- using the same technqiue as the last question you asked, invert one of the fractions and multiply them together (producing a division instead of a multiplication)
2007-01-26 10:46:16
·
answer #4
·
answered by mdigitale 7
·
0⤊
0⤋
-3 (-x-1) - 2x
--------------------
(x+1)(-x-1)
________________
-10 + 4(x+1)
--------------------
x+1 by having the same denominator
=3x+1 - 2x x+1
--------------- * -----------
(x+1)(-x-1) -6+4x
= x+1
------------
(-x-1) (-6+4x) (by cancelling the (x+1) from the numerator and denominator
= x+1
--------
-1(x+1) (-6+4x) cancel the x+1 from numerator and denominator
= 1 / (4x-6)
2007-01-26 10:55:14
·
answer #5
·
answered by K J 1
·
0⤊
0⤋
Here's a better one.
You + Posting math problems on yahoo questions = lame.
2007-01-26 10:47:30
·
answer #6
·
answered by Soundguy 2
·
0⤊
2⤋
one is the loneliest number
enough with the math porn already, I'll report you
2007-01-26 10:46:55
·
answer #7
·
answered by kurticus1024 7
·
1⤊
1⤋
ummmmm i honestly dnt give a crap
2007-01-26 10:47:15
·
answer #8
·
answered by Anonymous
·
0⤊
2⤋
hm, ask your teacher. ^_^
2007-01-26 10:47:32
·
answer #9
·
answered by Anonymous
·
0⤊
2⤋